Philippines : 2010 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Philippines. (IMF Staff Country Reports; Country Report ;, 2011)
After the global financial crisis, economic growth of the Philippines has increased. However, renewed shocks to global growth and financial markets would affect Philippine exports and remittances. The Bangko Sentral ng Pilipinas (BSP) appropriately has started to unwind its liquidity support measures since early 2010. Traditional toolkits are available for managing external inflows. The planned gradual withdrawal of fiscal stimulus and the focus on medium-term consolidation are welcomed. Public-private partnership programs can play an important role, and a medium-term Philippine development plan could also be prepared.